2020
DOI: 10.1128/jvi.00649-20
|View full text |Cite
|
Sign up to set email alerts
|

Serpentoviruses: More than Respiratory Pathogens

Abstract: In recent years nidoviruses have emerged as important respiratory pathogens of reptiles, affecting captive python populations. In pythons, nidovirus (recently reclassified as serpentovirus) infection induces an inflammation of the upper respiratory and alimentary tract which can develop into a severe, often fatal proliferative pneumonia. We observed pyogranulomatous and fibrinonecrotic lesions in organ systems other than the respiratory tract during full post mortem examinations on 30 serpentovirus RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 53 publications
(103 reference statements)
1
27
0
Order By: Relevance
“…Experimental infection of P. regius resulted in histological findings consistent with a chronic-active mucinous rhinitis, stomatitis, tracheitis, oesophagitis, and proliferative interstitial pneumonia ( 55 ). The proliferative interstitial pneumonia has been a consistent finding in clinical cases of nidovirus infection in snakes and has more recently been called “nidovirus associated proliferative disease—NPD” ( 16 , 57 ).…”
Section: Clinical Signs Pathology and Tissue Tropismmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental infection of P. regius resulted in histological findings consistent with a chronic-active mucinous rhinitis, stomatitis, tracheitis, oesophagitis, and proliferative interstitial pneumonia ( 55 ). The proliferative interstitial pneumonia has been a consistent finding in clinical cases of nidovirus infection in snakes and has more recently been called “nidovirus associated proliferative disease—NPD” ( 16 , 57 ).…”
Section: Clinical Signs Pathology and Tissue Tropismmentioning
confidence: 99%
“…Stenglein et al ( 16 ) identified virus in liver, kidney, heart, spleen, and brain, but largely at levels 3–5 orders of magnitude lower than the lung. More recently, during multiple necropsies ( n = 30) Dervas et al ( 57 ) identified pyogranulomatous and fibrinonecrotic lesions in organ systems aside from the respiratory tract suggesting a much broader cell and tissue tropism. Virus was also detected in epithelial cells (alimentary, hepatic, renal, pancreatic), intravascular monocytes, intralesional macrophages, and endothelial cells ( 57 ).…”
Section: Clinical Signs Pathology and Tissue Tropismmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, some pythons that were consecutively tested for over two years were continuously positive for serpentovirus but never exhibited clinical signs during this time [ 16 ]. In a separate study, systemic lesions associated with viral infection were observed in some pythons without clinical or histologic evidence of respiratory disease [ 34 ]. The findings in chameleons could represent similar phenomena as some animals shown to be infected did not develop disease, even over the three months prior to culling for herd health, and exhibited minimal to no histologic lesions (VC7, 8, 9).…”
Section: Discussionmentioning
confidence: 99%